2000
DOI: 10.1093/hmg/9.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Significant evidence for linkage of febrile seizures to chromosome 5q14-q15

Abstract: Febrile seizures (FSs) represent the most common form of childhood seizure. In the Japanese population, the incidence rate is as high as 7%. It has been recognized that there is a significant genetic component for susceptibility to this type of seizure. Two putative FS loci, FEB1 (chromosome 8q13-q21) and FEB2 (chromosome 19p), have been mapped. Furthermore, a mutation in the voltage-gated sodium (Na(+))-channel beta1 subunit gene ( SCN1B ) at chromosome 19q13.1 was identified in a family with a clinical subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 29 publications
0
67
1
2
Order By: Relevance
“…Although there is clear evidence for a genetic basis of FS, the mode of inheritance is unclear. Most convincing evidence has emerged from linkage studies with reported linkages on numerous chromosomes (2q, 48 5q, 49 53 ), with the strongest linkage on chromosome 2q and specifically, linkage to the genes responsible for sodium channel receptors-and specifically a mutation in the alpha (a) subunit of the first neuronal sodium channel gene (SCNIA). The linkage on chromosomes 2q and 19q associated with the phenotype of febrile seizures, generalised epilepsy (tonic-clonic, absence, and myoclonic), and a continuation of febrile seizures (.5 years of age) (GEFS+), 44 54 shows evidence of sodium channel involvement.…”
Section: The Genetics Of Febrile Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is clear evidence for a genetic basis of FS, the mode of inheritance is unclear. Most convincing evidence has emerged from linkage studies with reported linkages on numerous chromosomes (2q, 48 5q, 49 53 ), with the strongest linkage on chromosome 2q and specifically, linkage to the genes responsible for sodium channel receptors-and specifically a mutation in the alpha (a) subunit of the first neuronal sodium channel gene (SCNIA). The linkage on chromosomes 2q and 19q associated with the phenotype of febrile seizures, generalised epilepsy (tonic-clonic, absence, and myoclonic), and a continuation of febrile seizures (.5 years of age) (GEFS+), 44 54 shows evidence of sodium channel involvement.…”
Section: The Genetics Of Febrile Seizuresmentioning
confidence: 99%
“…There is currently no evidence that any of these loci have any role in the more common, ''simple'' FS, with the possible exception of the chromosome 5 locus reported in the Japanese population. 49 Clearly, febrile seizures are an extremely heterogeneous condition with a complicated and, as yet, unclear pathophysiological and genetic basis. 55 …”
Section: The Genetics Of Febrile Seizuresmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] Two loci originally described as FS loci (FEB3 and FEB4) were reported in pedigrees best classified as GEFSϩ due to phenotypes beyond typical FS. 20,21,27 Here we describe a GEFSϩ kindred from Central America with evidence for linkage to chromosome 6q16. 3-22.31.…”
mentioning
confidence: 96%
“…Wallace et al [24] [16]. Unabhängig von dieser Untersuchung gelang erst kürzlich 2 unabhängi-gen Arbeitsgruppen die Identifikation eines Erkrankungsgens in jeweils einer Familie, in denen Fieberkrämpfe im Zusammenhang mit fieberunabhängigen epileptischen Anfällen gehäuft auftraten.…”
Section: Molekularbiologische Untersuchungen Bei Fieberkrämpfenunclassified